Fermented soy product supplemented with isoflavones affected fat depots in juvenile rats - Manzoni, Marla S. J.; Rossi, Elizeu Antonio [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Vendramini, Regina Célia [UNESP]; Duarte, Ana Cláudia Garcia de Oliveira [UNESP]; Dâmaso, Ana R. (Elsevier, 2005)
Objectives: This study investigated the effects of soy product fermented by Enterococcus faecium and Lactobacillus jugurti supplemented with isoflavones on adipose tissue, blood lipid, and glucose levels on juvenile rats. Methods: Rats were fed a cholesterol-enriched diet for 3 wk as a preliminary treatment to create hypercholesterolemia. They were then fed a chow diet (HC), a chow diet plus fermented soy product supplemented with isoflavones (HCFI), a chow diet plus placebo (HCP), or a chow diet plus placebo supplemented with isoflavones (HCPI), respectively, for an additional 3 wk. Results: The beneficial effects of fermented soy product supplemented with isoflavones on epididymal (EPI) and retroperitoneal (RET) fat pads was likely due to isoflavones because adipocyte circumference (micrometers) in the HC group was significantly larger (EPI: 105.66 ± 13.36; RET: 134.95 ± 25.40) than that in the HCFI group (EPI: 93.17 ± 12.80; RET: 108.62 ± 15.50) and HCPI group (EPI: 93.06 ± 15.10; RET: 112.34 ± 18.21). The probiotic micro-organism accentuated the antilipogenic effect of isoflavones on RET (HCFI: 108.62 ± 15.50 micrometers versus HCPI: 112.34 ± 18.21 micrometers). Moreover, the fermented product increased glucose concentration similar to that in the chow group but did not change blood lipids. Conclusion: This product may offer new approaches to obesity prevention. © 2005 Elsevier Inc. All rights reserved.
Keywords: Adipose tissue; Fermented soy product; Isoflavones; Lipid and glucose levels; Obesity; Probiotic; glucose; isoflavin; isoflavone; lipid; probiotic agent; adipocyte; adipose tissue; animal cell; animal experiment; animal model; animal tissue; cell size; cholesterol diet; controlled study; Enterococcus faecium; epididymis fat; fermentation; fermented product; glucose blood level; hypercholesterolemia; Lactobacillus; lipid blood level; lipid storage; lipolysis; male; microorganism; nonhuman; obesity; priority journal; rat; retroperitoneum; soybean milk; Adipocytes; Adipose Tissue; Animals; Blood Glucose; Cell Size; Fermentation; Hypercholesterolemia; Lipids; Male; Probiotics; Random Allocation; Rats; Rats, Wistar; Soybeans